KEWENANGAN PRESIDEN DALAM KONSIL KEDOKTERAN INDONESIA (ANALISA PUTUSAN MAHKAMAH AGUNG NO.128/PK/TUN/2022) - Jaka Kusnanto W; Dafianto Arief; Effri Susanto; Charles Siagian; Retno Ambarsari; Elviera Melany (JURNAL DARMA AGUNG, 2023)
The President's duties and authority must be based on Basic and recognized law, Otherwise, it’s illegitimate. The Indonesian Medical Council is an autonomous, independent, nonstructural, aimed at protecting the community and improving the quality of health services. Supreme Court Decision No.128 PK/TUN/2022, void Presidential Decree No.55/M/Year2022, requires the President to revoke and issue new decision. Problem formulated: President authorities in the Indonesian Medical Council and existing regulations, with normative legal study methods. Principle hierarchy of Indonesia Legislations are Lex superiori derogat legi inferiori, Lex specialis derogat legi generali, Lex posteriori derogat legi priori, Regulations abolished with equal or higher. Appointment the Medical Council 2020-2025, material review Article 1 Permenkes No.81/2019 Amendments No.496/MENKES/PER/V/2008 “Procedures Proposing Candidates for Members The Indonesian Medical Council” contradicted Law No.29/2004 “Medical Practice”, so that Presidential Decree No.55/2020 was repealed.